Peran BPSDM dalam Pelaksanaan Latsar CPNS untuk Mendukung Pengembangan SDM Aparatur Pemerintah Provinsi - Nadia Sintya Bella; John Budiman Bancin; Nike Ardilla (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the role of the Central Kalimantan Provincial Human Resources Development Agency (BPSDM) in implementing the Civil Servant Candidate Basic Training (Latsar) to support the development of civil servant human resources. The study used a qualitative approach with descriptive methods, through interviews, observation, and documentation. The results indicate that BPSDM plays a role in three main aspects: planning, implementation, and evaluation of training. However, implementation still faces obstacles such as limited budget, human resources, coordination, and technical aspects, which impact the suboptimal quality of learning and evaluation. To address these challenges, adjustments were made to the learning method, strengthening the role of mentors, and improving the training system. Future developments will focus on the implementation of blended learning and digitalization of training. This research is expected to support the improvement of the quality of Latsar CPNS and the development of professional civil servants.